2023
DOI: 10.1155/2023/3758253
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Branch Spacing and Number on the Uplift Bearing Capacity of a New Squeezed Multiple-Branch Pile: A Numerical Simulation Analysis

Abstract: The squeezed multiple-branch pile is a variable section pile that was built by adding a bearing branch cavity to a constant section pile using expansion and extrusion equipment. It is widely used in engineering practice for its high bearing capacity, small settlement deformation, high economic benefits, strong adaptability, and simple pile forming process. In this paper, a new type of squeezed multiple-branch pile is proposed and its forming tool is invented. The forming tool of the pile has applied for an inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The branch enhances the effect of the pile-soil interaction by making full use of the mechanical properties of each layer of soil between the branches. Hence, the bearing capacity of the single square concrete in the pile is significantly improved so as to save on costs and shorten the construction period [6].…”
Section: Introductionmentioning
confidence: 99%
“…The branch enhances the effect of the pile-soil interaction by making full use of the mechanical properties of each layer of soil between the branches. Hence, the bearing capacity of the single square concrete in the pile is significantly improved so as to save on costs and shorten the construction period [6].…”
Section: Introductionmentioning
confidence: 99%
“…Prateep Lueprasert reveals the pile-soil-tunnel interaction mechanism behind tunnel deformation behavior by studying the influence of buildings with pile foundations on tunnels [6]. Su Qingqing used numerical simulation analysis and concluded that the appropriate number and spacing of the branches would maximize the bearing capacity of the branch pile and reduce the settlement [7]. Zhang Minxia et al analyzed the influence of branch position, spacing, number, and diameter on pile bearing capacity through numerical simulation, as well as the bearing behavior and failure mechanism of squeezed branch piles [8].…”
Section: Introductionmentioning
confidence: 99%